The Role of Nonhuman Primates in Neurotoxicology Research: Preclinical Models and Experimental Methods. Issue 3 (13th March 2023) - Petroff, Rebekah L.; Grant, Kimberly S.; Burbacher, Thomas M.
Abstract: Although noteworthy progress has been made in developing alternatives to animal testing, nonhuman primates still play a critical role in advancing biomedical research and will likely do so for many years. Core similarities between monkeys and humans in genetics, physiology, reproduction, development, and behavior make them excellent models for translational studies relevant to human health. This unit is designed to specifically address the role of nonhuman primates in neurotoxicology research and outlines the specialized assessments that can be used to measure exposure‐related changes at the structural, chemical, cellular, molecular, and functional levels. © 2023 Wiley Periodicals LLC.